Aplikasi mikroorganisme lokal bonggol pisang pada pertumbuhan dan hasil cabai merah (Capsicum annum L.) Varietas Gada F1 - Nine Wahyuni Maulani; Lusiana; Regawati (Fakultas Pertanian Universitas Majalengka, 2023)
This study aims to determine the dose of banana weevil microorganisms that affect the growth and yield of red chili (Capsicum annum L.). Cultivar Gada F1. This research was conducted in the Bunder Block, Subang District, Subang Regency, Dangdeur Village, West Java Province. This research was conducted in September - December 2022. The experiment was conducted using the experimental method and the design used was a simple randomized block design (RBD) consisting of five treatments and each was repeated five times. Each plot had 6 plant populations planted in polybags and four plant samples, so the total population was 5 x 5 x 6 = 150. The treatment in this experiment consisted of: P1 (100 mL), P2 (125 mL), P3 (150 mL), P4 (175 mL), P5 (200 mL). The parameters observed in this study included: plant height, plant dry weight, fruit diameter, fruit length, fruit number and fruit weight. Dosage of banana weevil microorganisms affects the growth and yield of red chili plants, namely in the parameters: plant height, fruit length, fruit number, and fruit diameter. Dose of 200 mL/ Polybag produces the best amount of fruit. Keywords: Local Microorganisms, Banana Weevil, Chili